Estudo quantitativo da lágrima pelo teste de fenol vermelho na população brasileira - Hida, Richard Yudi; Nishiwaki-Dantas, Maria Cristina; Hida, Milton Massato [UNESP]; Tsubota, Kazuo (FapUNIFESP (SciELO), 2005)
Purpose: To detect normal values of red phenol thread test in the Brazilian population and compare it between different races, age and sex. Methods: 280 white individuals (560 eyes) and 280 non-white individuals (560 eyes) were analyzed regarding sex and age, and analyzed using the Phenol Red test. Individuals with ocular diseases, contact lens or ocular drug users were excluded from this study. Results: Of the 1,120 evaluated eyes, the mean ± standard deviation result was 19,77±7,90 mm. Conclusion: The mean result found in this study was an intermediate value compared to the previously studied populations (Japanese and American).
Quantitative tear study using the red phenol test in the Brazilian population
Keywords: Comparative study; Cornea; Cross-cultural comparison; Diagnostic techniques; Dry eye syndromes; Ophthalmological; Osmolar concentration; Phenolsulfonphthalein/diagnostic use; Tears; phenol; phenolsulfonphthalein; Brazil; comparative study; controlled study; cornea; diagnostic procedure; dry eye; human; lacrimal fluid; lacrimation; osmolarity; race difference; sex difference; visual system examination; Adolescent; Adult; Age Distribution; Aged; Child; Child, Preschool; Coloring Agents; Dry Eye Syndromes; Ethnic Groups; Female; Humans; Infant; Infant, Newborn; Male; Middle Aged; Osmolar Concentration; Phenolsulfonphthalein; Reference Values; Sensitivity and Specificity; Sex Distribution; Statistics, Nonparametric